2018
DOI: 10.2147/ccid.s127841
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent candidal intertrigo: challenges and solutions

Abstract: Intertrigo is a common inflammatory dermatosis of opposing skin surfaces that can be caused by a variety of infectious agents, most notably candida, under the effect of mechanical and environmental factors. Symptoms such as pain and itching significantly decrease quality of life, leading to high morbidity. A multitude of predisposing factors, particularly obesity, diabetes mellitus, and immunosuppressive conditions facilitate both the occurrence and recurrence of the disease. The diagnosis of candidal intertri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 77 publications
(76 reference statements)
1
40
0
2
Order By: Relevance
“…Its change of status from commensal to pathogenic depends on the slight change of environmental conditions leading to expression of virulence factors like adhesins and invasins on its cell surface, production of hydrolases that mediate adhesion to susceptible host and biofilms formation as reported by Mayer et al (2013). C. albicans is also associated with interdigital space infection and found to be conformed to the findings of Metin et al (2018) which indicated that C. albicans, has a strong predilection for the intertriginous areas of the inguinal folds, intergluteal cleft, axillae, inframammary folds, umbilicus and the web spaces, particularly between the third, fourth, and fifth digits of the hands or feet.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Its change of status from commensal to pathogenic depends on the slight change of environmental conditions leading to expression of virulence factors like adhesins and invasins on its cell surface, production of hydrolases that mediate adhesion to susceptible host and biofilms formation as reported by Mayer et al (2013). C. albicans is also associated with interdigital space infection and found to be conformed to the findings of Metin et al (2018) which indicated that C. albicans, has a strong predilection for the intertriginous areas of the inguinal folds, intergluteal cleft, axillae, inframammary folds, umbilicus and the web spaces, particularly between the third, fourth, and fifth digits of the hands or feet.…”
Section: Discussionsupporting
confidence: 67%
“…The frequent isolation of C. albicans justifies its pathogenicity and is supported by the presence of underlying predisposing factors such as cancer, diabetes, prolonged use of antibiotics, hormonal therapy, oral contraception and pregnancy as reported by Metin et al (2018). The global burden of superficial fungal infection (skin, hair and nail) was put to approximately one billion and is mostly associated with candida clade with C. albicans on the lead in causing mucosal disease, Trichophyton in skin diseases and Aspergillus fumigatus in allergic fungal disease (Bongomin et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…This interesting finding is potentially attributable to the alteration with the aging of the dominant species Streptococcus, from probiotic communities to the conditional pathogenic genera. Because the skin barriers of the children and elder groups exist in an immature and recessive status, respectively, we detected a higher abundance of some conditional pathogenic genera, such as Neisseria, Streptococcus (elder group), and Candida (Petry et al, 2012;Beatrous et al, 2017;Metin et al, 2018). According to the clinical parameters, these species could be regarded as accelerators (negative correlations) of aging.…”
Section: Specific Age-related Microbial Communities and Pathways To Rmentioning
confidence: 82%
“…Positioned as the 4th most prevalent dermatological pathology in the last years and affecting 20‐25% of the world's population, they cause high morbidity rates . Their main aetiological agents are dermatophytic filamentous fungi and yeast such as Candida spp …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Their main aetiological agents are dermatophytic filamentous fungi and yeast such as Candida spp. 7,8 Dermatophytes are keratinophilic fungi, comprising species of three anamorphic genera-Microsporum, Trichophyton and Epidermophyton. 7,9 Trichophyton rubrum, Trichophyton mentagrophytes and more recently Microsporum canis have been identified as a biofilm-forming species, which worsens the therapeutic response.…”
Section: Introductionmentioning
confidence: 99%